The reality of educational supervision in following up the educational process based on distance education in the city of Jeddah from the supervisors' point of view - Al-Shehri, Amal Ali Mofraq; Al-Harbi, Rabab (Journal of Educational and Psychological Sciences, 2024)
The study aimed to explore the role of educational supervision in monitoring the distance learning process in Jeddah from the perspective of supervisors and to identify differences based on variables such as academic qualification, specialization, and experience. A descriptive methodology was employed, using a three-axis questionnaire distributed to a sample of 180 educational supervisors from Jeddah’s Education Directorate. Key findings revealed that educational supervision plays a significant role in monitoring the distance learning process in Jeddah. High levels of barriers to effective supervision were also noted, alongside strong agreement among supervisors regarding the requirements for implementing effective educational supervision. The highest-rated requirements were legislative, followed by training, and finally, financial and material needs, all rated as significant. No statistical differences were found in the supervisors’ responses regarding the role or barriers of educational supervision attributable to academic qualifications. However, differences in requirements were noted in favor of those holding a master’s degree or higher. Additionally, no statistically significant differences were observed in responses related to the role, barriers, or requirements of educational supervision based on specialization or years of experience. Based on these findings, the researcher recommended enhancing the role of educational supervision in distance learning, addressing barriers, and meeting the legislative, training, financial, and material needs identified in the study.
Keywords: educational supervision; learning process; distance education; educational supervisors